A specialist, second-tier response to out-of-hospital cardiac arrest: setting up TOPCAT2. Issue 5 (30th January 2013) - Clarke, Scott; Lyon, Richard M; Short, Steven; Crookston, Colin; Clegg, Gareth R
Abstract : Background: Out-of-hospital cardiac arrest (OHCA) is the most common, immediately life-threatening, medical emergency faced by ambulance crews. Survival from OHCA is largely dependent on quality of prehospital resuscitation. Non-technical skills, including resuscitation team leadership, communication and clinical decision-making are important in providing high quality prehospital resuscitation. We describe a pilot study (TOPCAT2, TC2) to establish a second tier, expert paramedic response to OHCA in Edinburgh, Scotland. Methods: Eight paramedics were selected to undergo advanced training in resuscitation and non-technical skills. Simulation and video feedback was used during training. The designated TC2 paramedic manned a regular ambulance service response car and attended emergency calls in the usual manner. Emergency medical dispatch centre dispatchers were instructed to call the TC2 paramedic directly on receipt of a possible OHCA call. Call and dispatch timings, quality of cardiopulmonary resuscitation and return-of-spontaneous circulation were all measured prospectively. Results: Establishing a specialist, second-tier paramedic response was feasible. There was no overall impact on ambulance response times. From the first 40 activations, the TC2 paramedic was activated in a median of 3.2 min (IQR 1.6–5.8) and on-scene in a median of 10.8 min (8.0–17.9). Bimonthly team debrief, case review and training sessions were successfully established. OHCA attended by TC2 showed an additional trend towards improved outcome with a rate of return of spontaneous circulation of 22.5%, compared with a national average of 16%. Conclusions: Establishing a specialist, second-tier response to OHCA is feasible, without impacting on overall ambulance response times. Improving non-technical skills, including prehospital resuscitation team leadership, has the potential to save lives and further research on the impact of the TOPCAT2 pilot programme is warranted.